Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/vco.12042
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive local therapy combined with systemic chemotherapy provides long‐term control in gradeIIstage 2 canine mast cell tumour: 21 cases (1999–2012)

Abstract: This retrospective case series evaluates the outcome of 21 dogs with grade II stage 2 mast cell tumour (MCT) treated with adequate local therapy and adjuvant systemic chemotherapy (prednisone, vinblastine and CCNU). The median survival for all dogs was 1359 days (range, 188–2340). Median disease-free interval was 2120 days (149–2325 days). Dogs treated with surgery and chemotherapy had shorter survival (median, 1103 days; 188–2010 days) than those that underwent surgery, radiation therapy and chemotherapy as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 72 publications
(109 reference statements)
0
53
0
Order By: Relevance
“…Dogs with more usual cutaneous MCTs also have been reported to have a poorer outcome when lymph node metastasis is present, which is intuitive given this typically implies a more aggressive biological behaviour. While there does appear to be a subset of MCT patients with stage 2 disease that have protracted survivals with therapy, however, most of these patients had intermediate‐grade tumours …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs with more usual cutaneous MCTs also have been reported to have a poorer outcome when lymph node metastasis is present, which is intuitive given this typically implies a more aggressive biological behaviour. While there does appear to be a subset of MCT patients with stage 2 disease that have protracted survivals with therapy, however, most of these patients had intermediate‐grade tumours …”
Section: Discussionmentioning
confidence: 99%
“…While there does appear to be a subset of MCT patients with stage 2 disease that have protracted survivals with therapy, 27 -29 however, most of these patients had intermediategrade tumours. 27,29 One drawback of the study is that metastatic nodes were diagnosed cytologically and very few were confirmed histologically. Mast cells can normally be found in lymph nodes, and it is notoriously difficult to distinguish true MCT metastasis from a reactive population of mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 Currently, the primary standard treatment for dogs with stage II cMCT comprises surgical excision of the primary tumour with or without radiation therapy (RT) and adjuvant medical treatment. [7][8][9] In this context, it has to be emphasized that the role of elective lymphadenectomy has historically been related to surgical staging for recognizing the true disease extent by detecting overt metastasis as well as pre-metastatic lesions. 3 However, the benefits of lymphadenectomy may extend beyond merely staging the burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Needless to say, an early detection of nodal metastasis is crucial for prompt and adequate therapeutic proposal, as well as for a correct staging and prognostication. It is accepted that palpation has a limited value in predicting LN metastasis in cMCT; similarly, cytology has been associated with a high proportion of both false positive and negative results . Furthermore, not all regional lymph nodes (RLNs) are feasible for immediate fine‐needle aspiration because of their anatomical location or size .…”
Section: Introductionmentioning
confidence: 99%